A Review on Safety and Outcomes of Mucous Fistula Refeeding in Neonates - Ghattaura, Harmit; Borooah, Manobi; Jester, Ingo (European Journal of Pediatric Surgery, 2020)
Introduction The utility of mucous fistula refeeding (MFR) in neonates with short bowel syndrome is widely debated. Our purpose is to review MFR and outline methods, reported complications, and clinical outcomes (survival, weight gain, dependence on parenteral nutrition [PN], and time to enteral autonomy).Materials and Methods We performed a MEDLINE literature search and reference review from January 1980 to May 2020 for terms (“mucous fistula re-feeding” or “enteral re-feeding”) and neonates. We included studies that utilized conventional MFR in the neonatal period. Non-English language articles were excluded.Results We identified 11 relevant articles. Internationally, there was no consensus on methods of MFR. A total of 197 neonates underwent MFR. Within a single study, four neonates developed major complications; however, the procedure was well tolerated without major complications in 10 of the 11 studies. A mortality of nine patients during MFR highlights the burden of disease within the study population; however, of these, only one was directly attributable to MFR. Minor complications were seldom quantified. Three studies demonstrated a higher rate of weight gain and shorter PN support versus controls. Neonates who underwent MFR had lower chance of anastomotic leak and quicker progression to full feed after reversal versus controls. The influence of microorganisms in MFR was only investigated in one study.Conclusion Current evidence suggests benefits of MFR; however, an international consensus is yet to be reached on the optimal method. A large prospective study investigating the influence of MFR on the enteric system is required.
Keywords: neonate; short bowel syndrome; mucous fistula refeeding; enteral refeeding; safety